Emerging perspective on judgment and decision research (Cambridge University Press, 2002)
This book exposes readers to a wide variety of new and promising perspectives for enhancing the scope of judgment and decision-making research. They bridge the gap between traditional paradigms and new lines of inquiry; expand awareness of new theories and approaches; and demonstrate how alternative approaches can enhance understanding.